2010
DOI: 10.1155/2010/392175
|View full text |Cite
|
Sign up to set email alerts
|

The Possibilities of Reduction of Polychlorinated Dibenzo-P-Dioxins and Polychlorinated Dibenzofurans Emission

Abstract: In the study the most important and known polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzo-furans (PCDFs) emission sources are presented and known methods of reduction of dioxin emission to the atmosphere are discussed in detail. It is indicated that the most relevant emission source is a combustion process. The mechanism of dioxin formation in thermal processes is presented in brief. The author characterized primary methods of reduction of PCDDs/PCDFs emission encompassing the interferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…Additionally, some studies have shown that coupled deNOx and dioxin destruction SCRs (Wang et al, 2009a), especially V-rich vanadia-tungsta-titania catalysts, are advantageous compared to only deNOx systems in terms of PCDD/F destruction and removal, but are still susceptible to deactivation by high chlorine content in the flue gases (Finocchio et al, 2006). Furthermore, these coupled deNOx and PCDD/F destruction, SCRs can compete with ACI (Finocchio et al, 2006), since the SCR systems destroy PCDD/Fs leading to reduction in PCDD/F mass (Wielgosinski, 2010;Ji et al, 2013).…”
Section: Pcdd/f Emissions From Sintering Plantsmentioning
confidence: 99%
“…Additionally, some studies have shown that coupled deNOx and dioxin destruction SCRs (Wang et al, 2009a), especially V-rich vanadia-tungsta-titania catalysts, are advantageous compared to only deNOx systems in terms of PCDD/F destruction and removal, but are still susceptible to deactivation by high chlorine content in the flue gases (Finocchio et al, 2006). Furthermore, these coupled deNOx and PCDD/F destruction, SCRs can compete with ACI (Finocchio et al, 2006), since the SCR systems destroy PCDD/Fs leading to reduction in PCDD/F mass (Wielgosinski, 2010;Ji et al, 2013).…”
Section: Pcdd/f Emissions From Sintering Plantsmentioning
confidence: 99%
“…Dioxins, including polychlorinated dibenzo-p-dioxins (PCDDs) and polychlorinated dibenzofurans (PCDFs), have been incorporated into the Annex C compounds of the Stockholm Convention (Stockholm Convention, 2006) due to their chemical properties of stability, lipophilicity and persistence. Therefore, various feasible and effective technologies for the control of dioxins emission are eagerly developing to prevent harmful influence on the environmental and human health (Wielgosiński, 2010;Wang et al, 2009;Chen et al, 2015). Previous studies indicate activated carbon injection technology has an excellent performance on the removal of gaseous PCDD/Fs, and thus has become a widely applied technology in the waste incinerators (Hajizadeh et al, 2011;Kawashima et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There are three basic mechanisms of their formation described in the literature: high-temperature synthesis (500-700°C) from chlorinated aromatic precursors [7], catalytic synthesis from chlorinated and non-chlorinated precursors and chlorinated compounds taking place at 300-500°C out of the combustion zone [8] and the most important one, the so-called de novo synthesis in which dioxins are formed outside the combustion zone from molecular carbon, carbonated residues from the combustion process, unburned carbon (in the form of dust and soot) and chlorine (both organic and inorganic) in the presence of volatile metals contained in the ash which catalyze the process (eg copper, zinc and aluminum) in the temperature range from 200 to 400°C [9]. There are many methods to reduce emissions of dioxins to the atmosphere which are described in detail in the literature [10,11]. Recently, the authors of many publications focused their attention on the reduction of dioxin emissions by reducing their formation according to the de novo mechanism.…”
Section: Introductionmentioning
confidence: 99%